The performance of nursing professionals in the health- disease process of children with oncological diseases: when death is present (Research, Society and Development, 2021)
This study aimed to analyze the scientific evidence about the performance of nursing professionals and their contribution to the terminal process of children with oncological disorders. The method was the integrative review, following the steps of Whittemore and Knalf, posing the following guiding question: What are the nursing contributions in the terminality process in children with oncological disorders? The search took place from May to November 2020, through the databases: BDENF, LILACS, MEDLINE and SciELO. Using the following descriptors: child, oncology nursing, death. Due to the limitation regarding the studies related to the theme, they were used as keywords. The criteria for the inclusion of articles were: qualitative, quantitative and theoretical studies, publications in Brazilian Portuguese and English and Spanish, published in the last 10 years, with free online access to the full text. Those works that were characterized as: theses, dissertations, texts in conference proceedings and publications that did not answer the guiding question were excluded from the final sample. Through the analysis and interpretation of the 8 selected articles, it was possible to understand the importance of the nursing professional in acting in pediatric oncology when death is present. It was understood that care goes beyond the procedures inherent to the profession, requiring a humanized look in order to develop skills such as welcoming the patient and family, respecting the autonomy of each individual and understanding that each human being who takes care of the other, also has its limitations in view of the finitude of life.